Peran Collaborative Interaction Women Leadership Terhadap Kinerja Karyawan: Studi Pada Usaha Mikro, Kecil, dan Menengah Banyumas - Daryono, Daryono (Faculty of Economics and Business | Universitas Diponegoro, 2024)
This study investigates the influence of women's leadership, perceived organizational support, and organizational justice on employee performance in women-led Micro, Small, and Medium Enterprises (MSMEs) in Banyumas Regency, Indonesia. It also explores the concept of Collaborative Interaction Women Leadership (CIWL) as a new paradigm in MSME leadership. Using a survey method with questionnaires, the research involved 81 MSME employees selected through purposive sampling. Results indicate that women's leadership and organizational justice have a significant positive impact on employee performance, while perceived organizational support shows no significant influence. This study uniquely contributes by integrating CIWL into the Indonesian MSME context, offering new perspectives on women's leadership in small and medium-sized enterprises. The findings provide valuable insights for policymakers and MSME practitioners in developing strategies to enhance employee performance through strengthening women's leadership and organizational justice. This research also contributes to a broader understanding of women's leadership roles in economic and social empowerment within the MSME sector, which plays a crucial role in Indonesia's economy.